YIELD AND CENTESIMAL AND MINERAL COMPOSITION OF NON-CARCASS COMPONENTS OF LAMBS FED DIETS CONTAINING MULBERRY HAY - Almeida, F. A. [UNESP]; Silva Sobrinho, A. G. [UNESP]; Santana, V. T. [UNESP]; Cirne, L. G. A.; Endo, V. [UNESP]; Borghi, T. H. [UNESP]; Zeola, N. M. B. L. [UNESP] (Inst Zootecnia, 2017)
The objective of this study was to evaluate the yield and centesimal and mineral composition of non-carcass components of lambs fed diets containing 0, 12.5 and 25.0% mulberry hay as concentrate substitute. Twenty-four uncastrated male Ile de France lambs with an initial body weight of 15 kg and final weight of 32 kg were used. The increase in mulberry hay in the diet exerted a quadratic effect on esophageal (R-2=1.0) and spleen weight (R-2=1.0), pulmonary iron content (R-2=0.94), calcium content of the heart (R-2=0.99), and sodium and potassium content of the kidneys (R-2=1.0). A linearly decreasing effect (R-2=0.98) was observed for skin and paws weight (R-2=0.93), and linearly increasing effect for copper content of the lung (R-2=1.0), sodium content of the liver (R-2=0.93), potassium content of the heart, (R-2=0.97) and iron content of the kidneys (R-2=0.77). There was a linearly increasing effect on most minerals in the tongue, except for magnesium, manganese and zinc. The centesimal composition of non-carcass components did not differ (P>0.05) between treatments. In conclusion, mulberry hay can be included at up to 25% in the diet of lambs without negatively altering the main quantitative and nutritional characteristics of non-carcass components of sheep.
Keywords: alternative feed; mineral; organs; sheep; viscera